2018
DOI: 10.1186/s12860-018-0159-y
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of LKB1/AMPK/mTOR metabolic axis response to global ischaemia in brain, heart, liver and kidney in a rat model of cardiac arrest

Abstract: BackgroundCellular energy failure in high metabolic rate organs is one of the underlying causes for many disorders such as neurodegenerative diseases, cardiomyopathies, liver and renal failures. In the past decade, numerous studies have discovered the cellular axis of LKB1/AMPK/mTOR as an essential modulator of cell homeostasis in response to energy stress. Through regulating adaptive mechanisms, this axis adjusts the energy availability to its demand by a systematized control on metabolism. Energy stress, how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…Beyond differences between cancer and normal cells, the effects of AMPK might generally be tissue-specific due to different metabolic profiles and needs. Majd et al [113] reported varying time courses and intensities of AMPK activation under short-term ischemia in rat brain, liver, kidney and heart that coincide with the individual tissue sensitivities to ischemic insults. This tissue specificity might be mediated by the different combinations of AMPK subunit isoforms [8] whose specific roles remain elusive for the most part to date [114] and might mirror the metabolic specificities of different tissues.…”
Section: Crosstalk Between Ampk and Hifmentioning
confidence: 99%
“…Beyond differences between cancer and normal cells, the effects of AMPK might generally be tissue-specific due to different metabolic profiles and needs. Majd et al [113] reported varying time courses and intensities of AMPK activation under short-term ischemia in rat brain, liver, kidney and heart that coincide with the individual tissue sensitivities to ischemic insults. This tissue specificity might be mediated by the different combinations of AMPK subunit isoforms [8] whose specific roles remain elusive for the most part to date [114] and might mirror the metabolic specificities of different tissues.…”
Section: Crosstalk Between Ampk and Hifmentioning
confidence: 99%
“…The AMPK pathway is considered to be the master regulator of cellular energy during conditions of metabolic stress because it can establish ATP homeostasis by both inhibiting ATP-consuming anabolic pathways and switching on catabolic pathways [25,26]. LKB1 is the upstream signal of AMPK and is one of the most important kinases mediating AMPK phosphorylation [7]. While the mTOR pathway is also an upstream signal of AMPK, the LKB1/AMPK pathway can negatively regulate the phosphorylation of the mTOR pathway [7].…”
Section: Disease Markersmentioning
confidence: 99%
“…LKB1 is the upstream signal of AMPK and is one of the most important kinases mediating AMPK phosphorylation [7]. While the mTOR pathway is also an upstream signal of AMPK, the LKB1/AMPK pathway can negatively regulate the phosphorylation of the mTOR pathway [7]. Considering the regulation of energy metabolism also reported in a recent study [7], we measured the effects of thyroxine on the phos-phorylation of the LKB1/AMPK/mTOR axis to determine the mechanisms by which thyroxine alleviates DOX-induced cardiac injury, and the results showed that thyroxine increased LKB1/AMPK phosphorylation but reduced mTOR phosphorylation in DOX-treated mice.…”
Section: Disease Markersmentioning
confidence: 99%
See 2 more Smart Citations